2012
DOI: 10.1097/grf.0b013e318253b318
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum Evaluation of the Fetus and Fetal Well Being

Abstract: Despite widespread use of many methods of antenatal testing, limited evidence exists to demonstrate effectiveness at improving perinatal outcomes. An exception is the use of Doppler ultrasound in monitoring high-risk pregnancies thought to be at risk of placental insufficiency. Otherwise, obstetricians should proceed with caution and approach the initiation of a testing protocol by obtaining an informed consent. When confronted with an abnormal test, clinicians should evaluate with a second antenatal test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Normal fetal heart rate tracings have a high predictive value for fetal wellness, with a false-negative rate of <1% 402 ; however, the positive predictive value for an abnormal test is fairly low. 401,402 Cardiotocography and nonstress testing are unlikely to be useful in fetuses with arrhythmias, particularly bradycardia and CHB, but may be considered as an adjunct to other monitoring in high-risk pregnancies with at-risk structural, functional, or rhythm-related fetal heart disease beginning in the third trimester and continuing periodically until delivery, although their usefulness has not been established.…”
Section: Cardiotocography and Nonstress Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal fetal heart rate tracings have a high predictive value for fetal wellness, with a false-negative rate of <1% 402 ; however, the positive predictive value for an abnormal test is fairly low. 401,402 Cardiotocography and nonstress testing are unlikely to be useful in fetuses with arrhythmias, particularly bradycardia and CHB, but may be considered as an adjunct to other monitoring in high-risk pregnancies with at-risk structural, functional, or rhythm-related fetal heart disease beginning in the third trimester and continuing periodically until delivery, although their usefulness has not been established.…”
Section: Cardiotocography and Nonstress Testingmentioning
confidence: 99%
“…This study showed no benefit, with an antepartum fetal death rate of 2.9 in 1000 in the intervention group versus 2.7 in 1000 in the control group. 400,401 Unfortunately, there are no such trials in high-risk pregnancies with fetal anomalies such as CHD or cardiac conditions that might put the fetus at risk as a result of hemodynamically unfavorable circumstances such as severe AV or semilunar valve regurgitation or arrhythmias. In populations with structural, functional, or rhythm-related CHD that put the fetus at risk for developing acidosis, it may be reasonable to encourage daily maternal movement assessments beginning at 26 to 28 weeks of gestation when movement can be reliably felt; however, the usefulness is not well established.…”
Section: Fetal Movement Assessment By Mother ("Kick Counts")mentioning
confidence: 99%
“…However, in over 500 United States Maternal‐Fetal Medicine members surveyed, 92% would recommend induction without documented lung maturity before 39 weeks, and 35% before 37 weeks, even though only one‐third of respondents felt induction would decrease adverse outcomes 75 , 76 . If expectant management is chosen, there is no consensus on what fetal monitoring is best, or even if fetal monitoring is necessary; however, the use of Doppler monitoring in pregnancies thought to be at risk of placental insufficiency has shown benefit 77 . Consistent maternal oral hydration can be encouraged.…”
Section: Dynamicsmentioning
confidence: 99%
“…If polyhydramnios is a late presentation, all the above should be considered, excluding an anatomical evaluation as this should have already been completed. Antenatal testing should be initiated at 24 weeks gestation, although there is no consensus on what type of testing should be begun, or at what interval 77 . This can be left to the discretion of the physician.…”
Section: Dynamicsmentioning
confidence: 99%
“…The American Congress of Obstetricians and Gynecologists states that the evaluation of fetal well-being may be appropriate for pregnancies with an increased risk of fetal involvement; however, there are no comprehensive trials demonstrating the benefit of all tests and their potential indications. On the other hand, experts recommend carrying out tests of fetal wellbeing in cases of diabetes, uterine growth restriction, and hypertension [7].…”
mentioning
confidence: 99%